Łukasiewicz on Causation - Riška, Augustín (Organon F, 2004)
In 1906, Łukasiewicz published a challenging proposal for the logical treatment of causal relations by means of the concepts of necessity and simple dependence. For this purpose he applied the law of transposition, well known in the propositional logic, combining it with modal considerations (necessity and non-necessity). In my historically motivated analysis of Łukasiewicz’s proposal, I suggest that he failed to separate the cause and effect relation from the relation between reasons and consequences, as well as to specify the modalities involved. Nevertheless, Łukasiewicz deserves credit for his pioneering attempt to treat the traditional philosophical problem of causation by the nontraditional means of the logic of relations.